2019
DOI: 10.1111/jpi.12581
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin stabilizes rupture‐prone vulnerable plaques via regulating macrophage polarization in a nuclear circadian receptor RORα‐dependent manner

Abstract: Rupture of vulnerable plaques is the main trigger of acute cardio-cerebral vascular events, but mechanisms responsible for transforming a stable atherosclerotic into a vulnerable plaque remain largely unknown. Melatonin, an indoleamine hormone secreted by the pineal gland, plays pleiotropic roles in the cardiovascular system; however, the effect of melatonin on vulnerable plaque rupture and its underlying mechanisms remains unknown. Here, we generated a rupture-prone vulnerable carotid plaque model induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
80
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(85 citation statements)
references
References 50 publications
(66 reference statements)
2
80
0
3
Order By: Relevance
“…It is generally accepted that the dose and dosing time are highly related to the efficacy of the pharmacological action of melatonin. The dose of 10 mg/kg ip (which produces far higher melatonin levels than normal physiological concentrations in the body) and the dosing time (9:00 am-9:30 am) used for melatonin treatment in the present study are comparable with those used in previous studies [64][65][66] and have been proven to be effective. It has been reported that melatonin can be tolerated at large doses by healthy humans and subjects with Parkinson's disease without any severe adverse effects.…”
Section: F I G U R E 1supporting
confidence: 65%
“…It is generally accepted that the dose and dosing time are highly related to the efficacy of the pharmacological action of melatonin. The dose of 10 mg/kg ip (which produces far higher melatonin levels than normal physiological concentrations in the body) and the dosing time (9:00 am-9:30 am) used for melatonin treatment in the present study are comparable with those used in previous studies [64][65][66] and have been proven to be effective. It has been reported that melatonin can be tolerated at large doses by healthy humans and subjects with Parkinson's disease without any severe adverse effects.…”
Section: F I G U R E 1supporting
confidence: 65%
“…From our analysis, we attempted to explain the result that higher NHR was associated with poorer clinical outcomes. Neutrophil was an indispensable component participating in the immuno-inflammatory response of AMI [33,34]. An increase in neutrophil has been verified at the site of coronary lesion [35].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, inflammation also activates both innate and adaptive immune responses involving monocytes/macrophages [5]. M1 macrophages promote plaque development, while M2 macrophages promote tissue repair and plaque stabilization [6]. More recently, Barrett reported that M1 macrophages are involved in initiating and sustaining inflammation, while M2 cells are implicated in inflammation resolution [7].…”
Section: Introductionmentioning
confidence: 99%